Resistance Analysis of Padi Gogo Merah (Oryza Nivara L) Against Blast Disease - Zulheri Noer; Deni Mudsan; Rizal Aziz; Ifan Aulia Candra (The University of Lampung, 2024)
Rice Blast has been known as the main disease on paddy which has high severity leading to economic loss. Exploring rice resistance can be an effective way to improve productivity and prosperity toward this staple crop. This study aims to determine several local varieties which have potential for productions and resistances. This study used factorial randomized block design (RBD) consisting of 2 factors including plant spacing (25 x 25 cm; 25 x 30 cm; 25 x 40 cm); Upland rice variety MSP 17, Sigambiri Merah, Hamparan Perak and Kambiri Lumat. The results of the study reveal that variety has a significant effect on disease intensity especially Sigambiri Merah but not on Kembiri Lumat. However, there is no significant effect of spacing on blast intensity except in grain weight. Conclusion of this research was the varieties (V) selection of red upland rice is the best strategy to improve rice resistance toward blast disease. Keywords: Disease density, Paddy, Staple Crop.